The river blindness drug Ivermectin and related macrocyclic lactones inhibit WNT‐TCF pathway responses in human cancer. Issue 10 (20th August 2014) - Melotti, Alice; Mas, Christophe; Kuciak, Monika; Lorente‐Trigos, Aiala; Borges, Isabel; Ruiz i Altaba, Ariel
Abstract Constitutive activation of canonical WNT‐TCF signaling is implicated in multiple diseases, including intestine and lung cancers, but there are no WNT‐TCF antagonists in clinical use. We have performed a repositioning screen for WNT‐TCF response blockers aiming to recapitulate the genetic blockade afforded by dominant‐negative TCF. We report that Ivermectin inhibits the expression of WNT‐TCF targets, mimicking dnTCF, and that its low concentration effects are rescued by direct activation by TCFVP16. Ivermectin inhibits the proliferation and increases apoptosis of various human cancer types. It represses the levels of C‐terminal β‐CATENIN phosphoforms and of CYCLIN D1 in an okadaic acid‐sensitive manner, indicating its action involves protein phosphatases. In vivo, Ivermectin selectively inhibits TCF‐dependent, but not TCF‐independent, xenograft growth without obvious side effects. Analysis of single semi‐synthetic derivatives highlights Selamectin, urging its clinical testing and the exploration of the macrocyclic lactone chemical space. Given that Ivermectin is a safe anti‐parasitic agent used by > 200 million people against river blindness, our results suggest its additional use as a therapeutic WNT‐TCF pathway response blocker to treat WNT‐TCF‐dependent diseases including multiple cancers.